Two Indonesian Mothers’ Journey in Nurturing Children’s Bilingual Development: From Practices to Aspects of Reflection - Maolida, Elis Homsini; Kurniawan, Eri; Noorman, Safrina; Amalia, Lulu Laela (Journal of English Teaching and Learning Issues, 2024)
This study presents the reflections of two Indonesian mothers working as EFL teachers on their experiences of fostering their children's bilingual development. It employed a narrative inquiry approach, gathering the participants' stories through oral and multimodal narratives. The mothers shared their stories during a semi-structured interview and through photos and videos. The findings reveal that the participating mothers introduced English to their children early by engaging them in natural English interactions and activities such as story reading before bed, hands-on activities, role-playing, games, and daily communication. Despite many similarities in activities, the consistency and continuity of providing exposure to English and Indonesian languages are different. The first mother implemented One Parent One Language Strategy (OPOL) with her child, using English with mother and Indonesian with father. On its journey, she shifted the strategy to Minority Language at Home strategy (MLaH) due to her husband’s passing with her child communicated English at home and learned Indonesian from school, relatives, and communities. Meanwhile, the second mother used English and Indonesian (mixing language strategy) to communicate with her daughter, using English as the dominant language. When her daughter started mixing the structure of the languages and experienced language confusion, the second mother minimized English use at home and shifted to using Indonesian as the dominant language at home. The findings also indicate that in nurturing children’s bilingualism, the mothers’ choices of practices involved five aspects of reflection: their philosophy, belief, theory, practice, and sociocultural aspect beyond practice. This study highlights that the process of nurturing children’s bilingual development is not a linear process. It involves a more complex relation of various factors that influence parents’ decision in (dis)continuing certain language policies.